Comparison of Indian ozonesonde and Umkehr profiles at New Delhi 1989-97 (MAUSAM, 2003)
Umkehr observations made with Dobson Spectrophotometer no.112  have been compared with Indian ozonesondes at New Delhi. Umkehr data are compared with ozone sonde data converted to the layer averaged format of the Umkehr profiles. Comparisons are made for seasonally, annually and long term averaged data. Results of comparison are shown to differ from season to season and year to year, but there is no long-term trend.